Efektivitas Web Based Inquiry Learning pada Materi Pencemaran Lingkungan dalam Konteks ESD (Education Sustainable Development) untuk Meningkatkan Kemampuan Berinkuiri dan Kepedulian Lingkungan Siswa SMP Kelas VII - Nuraeni Kamdi; Diana Rochintaniawati; Eka Cahya Prima (UNIB Press, 2022)
This paper examines research in using Web Based Inquiry Learning (WBIL) as an alternative to online inquiry learning during the COVID-19 pandemic. WBIL was built to assist junior high school students in understanding everyday science phenomena with a guided inquiry framework and various scaffolding sources. In addition, it aims to support teachers in designing their virtual inquiry classrooms for the new normal learning era. Learning using Web Based Inquiry Learning is effective in increasing students' inquiry abilities on environmental pollution material in the context of ESD (Educational Sustainable Development) which is marked by the results of the pretest and posttest data t-test calculations, obtained sig. 0.000 (0.000 < 0.05). While the results of the LKS analysis that students have done on the web with the average score on each indicator is 83.2% with a high interpretation. WBIL in environmental pollution is also effective in increasing students' environmental awareness, which is indicated by the average percentage of all indicators, there is an increase in the percentage from 74.5% to 79.0%.